Direct comparison of cardioprotective effects of necroptosis inhibitors against global ischemia-reperfusion in the isolated rat heart - Yu. V. Dmitriev; S. M. Minasian; V. K. Bayrasheva; E. A. Demchenko; M. M. Galagudza (Бюллетень сибирской медицины)
The study was aimed at comparative assessment of cardioprotective properties of various necroptosis inhibitors in the isolated perfused rat heart subjected to global ischemia-reperfusion.Materials and Methods. The study was performed on 38 male Wistar rats weighting 250–300 g. The following necroptosis inhibitors were tested: necrostatin-1 (Nec-1), necrostatin-5 (Nec-5), necrostatin-1s (Nec1s), and necrosulfonamide (NSA). All tested substances were administered intraperitoneally (i.p.) 1 hour prior to heart perfusion. Control animals were treated either with the vehicle (dimethyl sulfoxide, DMSO) or with 0,9% sodium chloride solution (Controls). The dose of necroptosis inhibitors was calculated on the basis of effective concentration (EC50) data. One hour after i.p. injection, the animals were anesthetized, the hearts were rapidly excised, the aorta was cannulated and retrogradely perfused according to Langendorff. After stabilization, the perfusion was stopped for 35 minutes, which was followed by 2 hours of reperfusion. Prior to stabilization, fluid-filled polyethylene balloon was placed into the left ventricle for left ventricular pressure registration. Coronary flow was measured at baseline and during reperfusion by means of perfusate collection. The volume of necrotic myocardium was expressed as a percentage of triphenyltetrazolium chloride-negative tissue relative to the entire heart volume.Results. The volume of myocardial necrosis and functional heart parameters were not different between Controls and DMSO group. All tested necroptosis inhibitors demonstrated infarct-limiting effect. However, there were no differences between the groups. The volume of necrotic myocardium was (50,5 ± 7,82)%, (29,9 ± 3,42)%, (27,7 ± 3,42)%, (30,6 ± 3,82)%, and (34,7 ± 5,82)% in DMSO, Nec-1, Nec-5, Nec-1s, and NSA groups, respectively (p < 0,01 vs. DMSO group).Nec-1s and NSA were shown to improve functional recovery of the heart after ischemia. In particular, left ventricular developed pressure and coronary flow rate were higher in Nec-1s and NSA groups (p < 0,01 compared with Controls and DMSO), while end-diastolic pressure was lower in Nec-1s and NSA groups vs. Controls and DMSO (p < 0,01).Conclusions. It has been shown that Nec-1, Nec-5, Nec-1s, and NSA administration prior to global ischemiareperfusion results in comparable infarct size limitation. In addition to infarct size limitation, Nec-1s and NSA are able to improve postischemic left ventricular function. This fact, along with low toxicity and optimal EC50, makes Nec-1s and NSA perspective candidates for preclinical and clinical development as cardioprotective agents.